Crystal structures of glutamyl‐tRNA synthetase from Elizabethkingia anopheles and E. meningosepticum. Issue 8 (28th July 2022) - Brooks, Lauryn; Subramanian, Sandhya; Dranow, David M.; Mayclin, Stephen J.; Myler, Peter J.; Asojo, Oluwatoyin A.
Abstract : Elizabethkingia bacteria cause opportunistic infections in neonates, the elderly and the immunocompromised with mortality rates of up to 40%. The high‐resolution structures of glutamyl‐tRNA synthetase (GluRS) from E. meningosepticum and E. anopheles reveal similarities to bacterial GluRSs that can be exploited to accelerate rational drug discovery for these globally important emerging infectious Gram‐negative bacteria. Abstract : Elizabethkingia bacteria are globally emerging pathogens that cause opportunistic and nosocomial infections, with up to 40% mortality among the immunocompromised. Elizabethkingia species are in the pipeline of organisms for high‐throughput structural analysis at the Seattle Structural Genomics Center for Infectious Disease (SSGCID). These efforts include the structure–function analysis of potential therapeutic targets. Glutamyl‐tRNA synthetase (GluRS) is essential for tRNA aminoacylation and is under investigation as a bacterial drug target. The SSGCID produced, crystallized and determined high‐resolution structures of GluRS from E. meningosepticum ( Em GluRS) and E. anopheles ( Ea GluRS). Em GluRS was co‐crystallized with glutamate, while Ea GluRS is an apo structure. Em GluRS shares ∼97% sequence identity with Ea GluRS but less than 39% sequence identity with any other structure in the Protein Data Bank. Em GluRS and Ea GluRS have the prototypical bacterial GluRS topology. Em GluRS and Ea GluRS have similar binding sites and tertiary structures to other bacterial GluRSs that are promising drug targets. These structural similarities can be exploited for drug discovery.